Keberhasilan Serikat Petani Indonesia dalam Perjuangan Hak Asasi Petani Tahun 2001 - 2018 - Mujahid Widian; Nur Iman Subono (Universitas Medan Area, 2019)
This study analyzes the success of the Indonesian Farmers Union (SPI) in the peasant rights struggle during 2001 - 2016. This study uses the social movement integration aprproach which is an attempt to synthesize three dimensions / approaches: the structure of political opportunity; structure of social mobilization; and cultural framing. This study uses qualitative research methods with study case approach. The research data is sourced from interviews and documents and literature related to this study. The analysis indicates that the success of SPI in peasant rights struggles in 2001 - 2018 can be seen from the ratification of 'Declaration Peasant Rights and Other People Working in Rural Area' or UNDROP at the International level. This success can’t be separated from the role of each dimension / approach, namely a combination of factors of political openness in Indonesia, the success of the SPI in networking alliances at various levels (local-international), and the construction of ideas on the rights of farmers that can be accepted universal.